Analisis Desain Selexol Regenerator 241-T9029 Terhadap Integritas Struktur Akibat Beban Seismik Dan Beban Angin Pada Proyek Gas Development For The Unitization Of The Jambaran Tiung Biru Field - Ridho Nur Faturrachman; Moh. Miftachul Munir; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract – Pressure vessel is a structure which used for fluida storage wheter in gas or liquid form inmany kind of industries. Referred as pressure vessel because the pressure and temperature of thefluida inside the pressure vessel is different compared to pressure and temperature of atmosphereoutside of pressure vessel. This research started with calculating the plate thickness in every sectionbased on internal and external pressure consideration. After that, the next step is calculating themaximum deflection due to wind load and required plate thickness due to seismic load. Finally, thelast step is calculating the stress value that occurs in pressure vessel using hand calculation andANSYS method.The result shows that the largest required thickness based on internal and externalpressure is 0,875 in and 0,1875 in for the smallest. For maximum deflection calculation, the result is0,576 in based on Henry H. Bednar method and 4,09 in based on Dennis R. Moss method. In stressanalysis using hand calculation method, the largest result is 7.416,38 psi and 1.870,44 psi for thesmallest. On the other hand, the largest value of the stress analysis using ANSYS method is 7.832,76psi and 1.994,99 psi for the smallest.